2023
DOI: 10.5194/acp-23-61-2023
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic and anthropogenic sources of isoprene and monoterpenes and their secondary organic aerosol in Delhi, India

Abstract: Abstract. Isoprene and monoterpene emissions to the atmosphere are generally dominated by biogenic sources. The oxidation of these compounds can lead to the production of secondary organic aerosol; however the impact of this chemistry in polluted urban settings has been poorly studied. Isoprene and monoterpenes can form secondary organic aerosol (SOA) heterogeneously via anthropogenic–biogenic interactions, resulting in the formation of organosulfate (OS) and nitrooxy-organosulfate (NOS) species. Delhi, India,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 143 publications
0
14
1
Order By: Relevance
“…The re‐analysis of different VOC observations collected over the last decade has shown the systematic presence of anthropogenic isoprene and monoterpenes in cities worldwide and also recently demonstrated in Delhi, India (Bryant et al., 2023). Here we show that monoterpenes, as well as isoprene, are potentially emitted at the exhaust of fossil fuel vehicles by re‐examining the DATAbASE data set and the literature and by collecting new observations in the developing world (Vietnam).…”
Section: Discussionmentioning
confidence: 94%
“…The re‐analysis of different VOC observations collected over the last decade has shown the systematic presence of anthropogenic isoprene and monoterpenes in cities worldwide and also recently demonstrated in Delhi, India (Bryant et al., 2023). Here we show that monoterpenes, as well as isoprene, are potentially emitted at the exhaust of fossil fuel vehicles by re‐examining the DATAbASE data set and the literature and by collecting new observations in the developing world (Vietnam).…”
Section: Discussionmentioning
confidence: 94%
“…Under the severe anthropogenic impacts, organic aerosols from anthropogenic sources (e.g., coal combustion, biomass burning) would result in an obvious elevation of the total OC concentrations, and biogenic VOC-derived OSs would occupy a relatively low fraction among organic aerosols. In Figure , the locations of (OSs + NOSs)/OM versus OC for some wintertime samples over the Bohai Sea overlapped with the region for the samples in polluted atmospheres (region C) in urban Beijing and Shanghai, China, or Delhi, India. , The sulfur content of the quantified OSs and NOSs elevated to >2% of those in nss-SO 4 2– in winter (Figure S8), which was mainly attributed to the increased contribution of monoterpene-NOSs (Figure S4). The influence of anthropogenic outflows on the atmospheric sulfur cycle over marginal seas in winter should be considered with organic sulfur involved.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings build on the work by Nelson et al and Bryant et al by focusing on the role NO plays in regulating OH and NO 3 radical concentrations within Delhi. 19,24 The unique chemistry investigated in this study deviates from our typical understanding of nocturnal radical oxidation chemistry and has important policy implications, highlighting the need to reduce nighttime NO x emissions alongside VOC emissions, to not further exacerbate PM and O 3 concentrations through secondary formation.…”
Section: ■ Introductionmentioning
confidence: 87%
“…The nature of radical chemistry at night, when pollution is high, may have significant consequences on the subsequent daytime oxidation chemistry and secondary pollution formation. A recent study by Bryant et al presented evidence of the removal of nighttime NO 3 radicals by NO in Delhi via a decrease in the concentration of isoprene-derived nitrooxy-organosulfate (NOSi) species produced via NO 3 oxidation chemistry . In addition, a study by Nelson et al, corroborated by Chen et al, found central Delhi to be VOC-limited with respect to O 3 production and significant titration of O 3 , owing to very high NO concentrations at night during the winter periods. , The ratio of NO x to non-methane VOCs has also been shown to impact rates of secondary organic aerosol formation .…”
Section: Introductionmentioning
confidence: 98%